Critical Analysis on the Performances of the IQ and General Knowledge among Graduates in the Northern Province of Sri Lanka - Nithlavarnan, A.; Sasikumar, V. (University of Jaffna, 2018)
Unemployment is a significant sustainability issue in Sri Lanka[1], [2].The number of unemployed graduates is higher than the other unemployed youths in the country[3], [4]. Several studies revealed that they do not have enough employability skills which are expected by the present employers in the government and private sectors[5], [6]. Commonly, competitive examinations for recruitment assess the performance of Intelligence Quotient (IQ) and General knowledge among candidates. This study attempts to examine the performance of IQ and General Knowledge among recently passed out graduates in Northern Province of Sri Lanka. For that purpose secondary data of 2459 graduates belonging to the Northern Province were obtained from the Web site of Northern Provincial Council. Chi-square statistical test was carried out to find out any association in Gender, Ethnic group, Permanent district, offered subjects Tamil, History, Civics, Geography, Information Technology (IT), Agriculture, Second Language, Media, English and Counseling with scoring at least 40 marks (Pass Score) in IQ. Same test was carried out to identify the association with scoring Pass Score in General Knowledge. The study revealed that the IQ has association individually with Ethnic group of graduates and with the offered subjects Tamil, History, Civics, IT, Agriculture and Counseling. At the same time General Knowledge has association individually with Gender and offered subjects Tamil, Geography, Second Language and Counselling. And also there was positive correlation between scoring in IQ and General Knowledge.